The persistence of ownership inequality. Investors on the German stock exchanges, 1869 – 1945 - Sibylle H. Lehmann-Hasemeyer; Andreas Neumayer (Humboldt University Berlin, 2018)
We study the ownership structure of joint-stock firms for the period of 1869 to 1945 based on a unique hand-collected data set. The data covers a selection of 785 general meetings of 276 firms, including details of more than 10,000 investors. We show that after the hyperinflation of 1923, when shares became cheaper, the ownership share among lower social classes rose significantly. Moreover, with the rise of women rights after 1919, the number of shares owned by women also increased significantly. However, despite these shifts, the majority of shares remained in the hands of institutional investors and investors from the upper class, who mainly constituted and controlled the general meetings. Thus, despite the increased participation of women and the lower social classes, a stark inequality of opportunities persisted.
urn:nbn:de:kobv:11-110-18452/20240-4
Keywords: 330; Stock exchanges; Investors; Characteristics; Investment behaviour; Stock exchanges; Investors; Characteristics; Investment behaviour